Scrub typhus with secondary hemophagocytic lymphohistiocytosis in a 3-month-old child from a tertiary care hospital of Odisha - Sanjay Kumar Sahu; Jyoti Ranjan Behera; Sushrith Kumar Yadav (Wolters Kluwer Medknow Publications, 2021)
Scrub typhus is one of the re-emerging infectious diseases in India, whereas hemophagocytic lymphohistiocytosis (HLH) results from an uncontrolled and ineffective hyperinflammatory response to a variety of triggers. HLH is categorized into primary and secondary type with infection being one of the leading causes of secondary HLH. Here, we report a case of 3-month-old girl diagnosed with scrub typhus associated with secondary HLH as both the age of presentation and the association are rarely reported in literature.